2004
DOI: 10.1785/0120030067
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Lasting Relaxation of Seismicity at Aswan Reservoir, Egypt, 1982-2001

Abstract: The Aswan reservoir seismicity is accepted as an example of reservoirinduced seismicity with the M 5.4 event of 1981, which occurred 15 years after the reservoir impoundment started. During the 1982-2001 period, the Aswan seismicity separates into shallow and deep seismic zones, between 0 and 15 and 15 and 30 km, respectively. These two seismic zones behave differently over time, as indicated by the seismicity rate, depth migration, b-value, and spatial clustering. For the deep events, the rate decreases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 32 publications
4
26
0
1
Order By: Relevance
“…Nonetheless the existence of fluids in the porous medium is required to simultaneously explain seismicity triggering and low resistivity. Mekkawi et al [18] showed that during a period of ten years after the occurrence of the M = 5.4 earthquake the seismicity of this region correlated with the lake level, implying the presence of fluids and delayed transfer of pore pressure. The delay is 120 days for deep seismicity and 60 days for the shallow activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless the existence of fluids in the porous medium is required to simultaneously explain seismicity triggering and low resistivity. Mekkawi et al [18] showed that during a period of ten years after the occurrence of the M = 5.4 earthquake the seismicity of this region correlated with the lake level, implying the presence of fluids and delayed transfer of pore pressure. The delay is 120 days for deep seismicity and 60 days for the shallow activity.…”
Section: Discussionmentioning
confidence: 99%
“…Annual level variations in Lake Aswan have been well correlated with the local seismic activity [18], suggesting that a transfer of hydrostatic pressure occurs through the faulted rocks. The goal of the current research is to confirm the presence of crustal fluids and thus, to explain the triggering mechanism for earthquakes occurring in this seismically active area; this was achieved by looking for a typical conductive signature of transcurrent faults such as the Kalabsha Fault [19].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…(Snaebjörnsson, et al 2006;Sigtryggsdóttir et al 2013b) TM Reservoirs may trigger RTEs. (Gupta 2002;Telesca et al 2012;ICOLD 2011) Reservoir (Res) (Gráková et al, 2007) ) IW (Muço, 2013 Pandey and Chadha (2003), Mekkawi (2004), Gupta (2002) d Def is abbreviation for deformation Nat Hazards (2003) …”
Section: Appendixmentioning
confidence: 99%
“…In all the other periods, the crosscorrelation coefficient was very small, leading to a generally weak relationship between the water fluctuations and seismicity. Mekkawi et al (2004) studied the 1982-2001 shallow (between 0 and 15 km) and deep (between 15 and 30 km) Aswan seismicity, finding that among all the possible seismic parameters, only the seismicity rate correlates with the seasonal fluctuations of the lake level, indicating positive evidence for the Aswan seismicity to be reservoir-triggered in the 1982-2001 period. Furthermore, time and space clusterization indicated that numerous aftershocks are activated, suggesting that the Aswan seismicity emerges both from the water level loading and the interplay between induced earthquakes themselves through the aftershock activation.…”
Section: Introductionmentioning
confidence: 99%